2021
DOI: 10.1126/sciadv.abf2400
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell shuttle for precise delivery of nanotherapeutics for heart disease and cancer

Abstract: The delivery of therapeutics through the circulatory system is one of the least arduous and less invasive interventions; however, this approach is hampered by low vascular density or permeability. In this study, by exploiting the ability of monocytes to actively penetrate into diseased sites, we designed aptamer-based lipid nanovectors that actively bind onto the surface of monocytes and are released upon reaching the diseased sites. Our method was thoroughly assessed through treating two of the top causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Earlier this year, our group published a study using therapeutic-loaded nanoparticles decorated with aptamers which were able to piggyback on the surface of immune cells and used them as a shuttle bus to target the heart following ischaemic injury and the pancreatic tumour site [ 26 ]. Both of these unrelated diseases with an entirely different pathophysiology had one aspect in common: following a myocardial ischaemia reperfusion episode and during tumour growth, monocytes are constantly recruited to these sites and, upon extravasation, will differentiate to become macrophages.…”
Section: Design and Fabrication Of Biomimetic Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier this year, our group published a study using therapeutic-loaded nanoparticles decorated with aptamers which were able to piggyback on the surface of immune cells and used them as a shuttle bus to target the heart following ischaemic injury and the pancreatic tumour site [ 26 ]. Both of these unrelated diseases with an entirely different pathophysiology had one aspect in common: following a myocardial ischaemia reperfusion episode and during tumour growth, monocytes are constantly recruited to these sites and, upon extravasation, will differentiate to become macrophages.…”
Section: Design and Fabrication Of Biomimetic Nanoparticlesmentioning
confidence: 99%
“…The treatment also successfully prolonged the survival of both groups of mice. Furthermore, when we used the nanoplatform to treat mice with liver metastasis, we found that the treatment successfully ameliorated the metastatic tumour burden and also increased their survival [ 26 ]. Since our strategy is not disease-specific, we believe that our nanoplatform can be used for the treatment of diseases that involve monocyte recruitment in the pathophysiology.…”
Section: Design and Fabrication Of Biomimetic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages are able to cross the vascular wall, co-delivering nano-carriers into the extravascular space, including to brain tumors [92,93]. This approach has been used by our group to design liposomes which use aptamer targeting to attach to monocytes and are then brought to tumor sites [62].…”
Section: Cells As Trojan Horse Carriers Of Nanomedicinesmentioning
confidence: 99%
“…These PHD2 inhibitors as HIFα stabilizers have received the most clinical success as an alternative treatment of anemia in patients with chronic kidney diseases by stimulating renal and hepatic erythropoietin production [ 17 ]. In addition, they have been demonstrated to be protective against ischemia-reperfusion injury in experimental ischemic diseases [ 18 , 19 , 20 ]. Recently, a growing body of evidence has linked aberrantly high PHD expression to several human cancers [ 21 , 22 , 23 ] and suggested that inhibiting PHD2 can be a potential therapeutic for cancer [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%